Therapeutic enhancement of blood–brain and blood–tumor barriers permeability by laser interstitial thermal therapy. Issue 1 (30th June 2020) - Salehi, Afshin; Paturu, Mounica R; Patel, Bhuvic; Cain, Matthew D; Mahlokozera, Tatenda; Yang, Alicia B; Lin, Tsen-Hsuan; Leuthardt, Eric C; Yano, Hiroko; Song, Sheng-Kwei; Klein, Robyn S; Schmidt, Robert; et al.
Abstract: Background: The blood–brain and blood–tumor barriers (BBB and BTB), which restrict the entry of most drugs into the brain and tumor, respectively, are a significant challenge in the treatment of glioblastoma. Laser interstitial thermal therapy (LITT) is a minimally invasive surgical technique increasingly used clinically for tumor cell ablation. Recent evidence suggests that LITT might locally disrupt BBB integrity, creating a potential therapeutic window of opportunity to deliver otherwise brain-impermeant agents. Methods: We established a LITT mouse model to test if laser therapy can increase BBB/BTB permeability in vivo. Mice underwent orthotopic glioblastoma tumor implantation followed by LITT in combination with BBB tracers or the anticancer drug doxorubicin. BBB/BTB permeability was measured using fluorimetry, microscopy, and immunofluorescence. An in vitro endothelial cell model was also used to corroborate findings. Results: LITT substantially disrupted the BBB and BTB locally, with increased permeability up to 30 days after the intervention. Remarkably, molecules as large as human immunoglobulin extravasated through blood vessels and permeated laser-treated brain tissue and tumors. Mechanistically, LITT decreased tight junction integrity and increased brain endothelial cell transcytosis. Treatment of mice bearing glioblastoma tumors with LITT and adjuvant doxorubicin, which is typically brain-impermeant, significantly increased animal survival. Conclusions: Together, these results suggest that LITT can locally disrupt the BBB and BTB, enabling the targeted delivery of systemic therapies, including, potentially, antibody-based agents.